An Insight into the Role of Periodontitis as a Potential Risk Factor for Development of Erectile Dysfunction - Mohd Sood, Zuhrah; Nik-Azis, Nik Madihah; Baharin, Badiah; Md Zainuddin, Zulkifli; Razali, Masfueh; Hussaini, Haizal Mohd (Archives of orofacial sciences, 2022)
Erectile dysfunction (ED) is one of the common sexual disorders affecting many men worldwide. Owing to shared common risk factors, periodontitis is related to ED. However, the prevalence of periodontitis among Malaysian patients with ED is currently unknown. This study aimed to investigate the prevalence of periodontitis in patients with ED in Malaysia and the factors associated with this relationship. Forty-one subjects aged 27–59 years old were recruited to participate in this study. The International Index of Erectile Function (IIEF-5) was used in assessing the presence of ED. Their periodontal health was assessed through comprehensive periodontal examination including plaque index, bleeding on probing and clinical attachment level. The subjects were categorised according to the severity of their periodontal health and ED. A questionnaire on general health and oral habits was administered. The prevalence of periodontitis (95.5%) among subjects with ED was significantly higher than those without ED (52.6%). Subjects with ED had the worst periodontal health, as indicated by the mean clinical attachment loss and percentage of sites with bleeding on probing. No differences in oral hygiene habits were found between subjects with and without ED. The prevalence of periodontal disease among Malaysian patients with ED was high. Periodontitis was positively associated with the severity of ED, supporting a dose-dependent association between the two diseases. Oral hygiene habits were not significantly related to any periodontitis parameters nor were significantly different between subjects with and without ED.